2020
DOI: 10.1063/5.0022968
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing droplet dispersal for face shields and masks with exhalation valves

Abstract: Several places across the world are experiencing a steep surge in COVID-19 infections. Face masks have become increasingly accepted as one of the most effective means for combating the spread of the disease when used in combination with social-distancing and frequent hand-washing. However, there is an increasing trend of people substituting regular cloth or surgical masks with clear plastic face shields and with masks equipped with exhalation valves. One of the factors driving this increased adoption is improv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 26 publications
2
108
1
9
Order By: Relevance
“…Laboratory studies have shown that both valved respirators and face shields are substantially less effective at blocking small airborne particles than either cloth or medical masks—the former because the valve (unless covered) effectively acts as an exhaust pipe and the latter because the shield may channel a powerful jet that escapes upward or downward ( 65 , 69 ).…”
Section: A Mask Needs To Block the Virus—and Be Comfortablementioning
confidence: 99%
“…Laboratory studies have shown that both valved respirators and face shields are substantially less effective at blocking small airborne particles than either cloth or medical masks—the former because the valve (unless covered) effectively acts as an exhaust pipe and the latter because the shield may channel a powerful jet that escapes upward or downward ( 65 , 69 ).…”
Section: A Mask Needs To Block the Virus—and Be Comfortablementioning
confidence: 99%
“…Examples of common PPE used in SRL include masks and other suitable face coverings, face shields, disposable gloves, clean lab coats, and safety goggles. Studies have shown effective reduction in the transmission of particulates through the use of masks (21). Various kinds of face shields and masks are available and reduce droplet spread to different degrees as assessed by physical testing (22).…”
Section: Human‐associated Risksmentioning
confidence: 99%
“…But since coughing and sneezing expels droplet and aerosols at high pressure, the general consensus is that face masks also protect others by capturing some, if not all, of the droplets and aerosols produced by the wearer. Penetration of droplets through the filter material, exhalation valves and around the face depends on the fit or seal of the mask (3). It is therefore assumed that filtration efficiency is reflective of the mask's efficacy in capturing droplets exerted by the mask wearer.…”
Section: European Standards Standalone Effectiveness and Anatomymentioning
confidence: 99%